2020
DOI: 10.1098/rspb.2019.2873
|View full text |Cite
|
Sign up to set email alerts
|

Ecological mechanisms explaining interactions within plant–hummingbird networks: morphological matching increases towards lower latitudes

Abstract: Interactions between species are influenced by different ecological mechanisms, such as morphological matching, phenological overlap and species abundances. How these mechanisms explain interaction frequencies across environmental gradients remains poorly understood. Consequently, we also know little about the mechanisms that drive the geographical patterns in network structure, such as complementary specialization and modularity. Here, we use data on morphologies, phenologies and abundances to explain interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 58 publications
12
81
1
1
Order By: Relevance
“…However, the result that empirical motif distributions are closer to those produced by an abundance model than a morphological matching model is surprising. Recent studies have found that the influence of niche‐based processes varies spatially (Sonne et al., 2020b) and that abundance may play a more important role than previously recognised (Simmons, Vizentin‐Bugoni, et al, 2019), which could explain our findings. Alternatively, our result could reflect the influence of different processes on different hierarchies of community structure.…”
Section: Discussionsupporting
confidence: 57%
“…However, the result that empirical motif distributions are closer to those produced by an abundance model than a morphological matching model is surprising. Recent studies have found that the influence of niche‐based processes varies spatially (Sonne et al., 2020b) and that abundance may play a more important role than previously recognised (Simmons, Vizentin‐Bugoni, et al, 2019), which could explain our findings. Alternatively, our result could reflect the influence of different processes on different hierarchies of community structure.…”
Section: Discussionsupporting
confidence: 57%
“…Overall, these results suggest a very mixed picture about how closely interaction frequency and abundance are related. These mixed findings are corroborated by our analysis of a plant-hummingbird network that includes independent abundance data [74][75][76] (S5 Analysis). We found that the relationship between observed interaction frequency and interaction probabilities determined by either empirical or idealised abundance distributions were only very weakly correlated.…”
Section: Interaction Propertiessupporting
confidence: 62%
“…trait matching model ; Sazatornil et al ., 2016). Both processes may generate subsets of interacting species (modules) and increase network modularity (Maruyama et al ., 2014; Sonne et al ., 2020). Furthermore, species abundances may also play a major role in defining interactions as abundant species have higher chances to find multiple partners, as well as to interact at higher frequencies, than rarer species – a process called neutrality (Vázquez et al ., 2009a; Vizentin‐Bugoni et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%